Efficacy and Safety of Taeeumjowi-tang in Obese Korean Adults: A Double-Blind, Randomized, and Placebo-Controlled Pilot Trial. (26th August 2013) - Park, Sunju; Nahmkoong, Won; Cheon, ChunHoo; Park, Jeong-Su; Jang, Bo-Hyoung; Shin, Yongcheol; Kim, Kyung-Soo; Go, Hoyeon; Song, Yun-Kyung; Ko, Seong-Gyu
Abstract : Objective . The purpose of this study was to assess the efficacy and safety of Taeeumjowi-tang (TJ001) as well as to estimate obesity-related factors. Methods . This was a 12-week trial with 5 visits. A total of 102 participants of both genders were randomized to either TJ001 (n = 57 ) group or the placebo group (n = 55 ). Subjects were administered 7 g of either TJ001 or placebo 3 times a day. The primary outcome was a rate of subjects who lost 5% or more of initial weight. Secondary outcomes included anthropometric parameters, lipid profiles, and body fat composition. Results . The subject response rate of ≥5% weight loss compared to baseline was similar in both groups, and no statistically significant difference was observed (P = 0.87 ). Changes in anthropometric parameters were greater during the first 4 weeks in the treatment group (P < 0.0001 ). There were no significant changes in both within groups and between groups for lipid profile and body fat composition. No adverse event was reported in either group. Conclusion . Although the difference between the groups regarding a rate of subjects who lost 5% or more of initial weight did not show statistical significance, TJ001 appears to be beneficial in safely controlling weight.